Determination of Germination Threshold Value of Chickpea Varieties with GGE Biplot Method Under Different Irrigation Water Salinity Conditions - Tülay Tütenocaklı; Yalçın Coşkun; Mevlüt Akçura; İsmail Tas (Journal of Agricultural Sciences)
For sustainable agricultural production, besides drought, plant resistance to irrigation water and soil salinity should be investigated. Researchers mostly focused on salinity and drought resistance of common species such as wheat, barley, maize, etc. However, the number of studies on chickpea with various uses is quite limited. In the present study, 11 chickpea varieties (Aksu, Arda, Hasanbey, Azkan, Cagatay, Aslanbey, Inci, Seckin, 21C, 42C and EN1867) were subjected to germination tests under different levels of irrigation water salinity (ECi) conditions to identify irrigation water salinity resistant and sensitive varieties. In germination tests, besides control treatment (0 dS/m), five different EC levels (6, 8 10, 12 and 16 dS/m) were used in germination solution. The sodium absorption ratio of saline waters was adjusted to be below 3. GGE biplot method was used for visual assessment of genotype response to saline irrigation waters. The threshold salinity value for germination was identified as 12 dS/m based on germination ratios and seedling dry weights, 8 dS/m based on seedling stem lengths and 10 dS/m based on seedling root lengths. Based on germination ratios and seedling dry weights, Azkan cultivar was identified as the most resistant and Cagatay cultivar was identified as the most sensitive cultivar to irrigation water salinity.